Determinants of Adolescent Posyandu Utilization in Stabat Primary Health Care, Indonesia - Rahmah Fadlilatu Syahadah; Fitriani Pramita Gurning (Karya Kesehatan Siwalima, 2026)
The Adolescent Posyandu Program is a government initiative aimed at improving adolescent health status. However, the utilization of adolescent posyandu services in the working area of the Stabat Public Health Center, Langkat Regency, remains low and has not yet reached the national target of 80%. This study aimed to analyze the factors influencing the utilization of adolescent posyandu services in this area. This study employed a quantitative approach with a cross-sectional design. A total of 94 adolescent respondents were selected using a stratified random sampling technique. Data were analyzed using the Chi-square test for bivariate analysis and logistic regression for multivariate analysis. The results showed that only 39 respondents (41.5%) utilized adolescent posyandu services. Bivariate analysis indicated significant associations between knowledge, attitudes, the role of health cadres, family support, and peer support with the utilization of adolescent posyandu services (p < 0.05). Multivariate analysis revealed that knowledge (p = 0.003), attitudes (p = 0.006), and peer support (p = 0.018) had a significant influence on utilization (p < 0.05). Among these variables, attitude was identified as the most dominant factor (Exp(B) = 25.047), indicating that adolescents with positive attitudes were significantly more likely to utilize posyandu services. In conclusion, attitudes, knowledge, and peer support play significant roles in influencing adolescent participation in posyandu programs, with attitude emerging as the strongest predictor. Strengthening health promotion strategies that focus on improving adolescents’ attitudes is essential to increase service utilization.